Partially thrombosed internal carotid artery: A diagnostic dilemma - Khanduri, Sachin; Kanojia, Avani; Habib, Archiya; Ahmad, Mugheer; Agrawal, Anmol; Patel, Nutan (Indian Journal of Case Reports, 2025)
Acute or chronic thrombosis of the internal carotid artery (ICA) is a rare but life-threatening condition that can result in ischemic stroke, transient ischemic attacks (TIAs), or significant neurological deficits. The ICA is a major blood vessel supplying oxygenated blood to the brain, and its occlusion can lead to devastating consequences, including cerebral infarction, hemodynamic insufficiency, and embolic complications. Acute thrombosis occurs suddenly, often due to embolism, arterial dissection, or hypercoagulable states, leading to abrupt-onset neurological symptoms such as hemiparesis, hemianesthesia, aphasia, or visual disturbances. It requires urgent intervention, including thrombolysis or mechanical thrombectomy. Chronic thrombosis develops over time, typically secondary to atherosclerosis or vessel narrowing, allowing collateral circulation to compensate. Patients may remain asymptomatic or experience gradual cognitive decline, TIAs, or progressive stroke-like symptoms.